CURRICULUM TRANSFORMATION FOR SANTRI IN RESPONSE TO INFORMATION AND COMMUNICATION TECHNOLOGY (ICT): LEADERS’ PERSPECTIVES - Muyassaroh (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2023)
This study aims at examining Curriculum transformation for santri of pesantren institutions at Mifthul Ulum and Al-Bukhori Gondanglegi Malang in response to Information and Communication Technology (ICT). Based on qualitative method employed it is discovered that these pesantren have conducted an adaptation process with ICT in the form of an administrative system such as payment of student fees, student data and lessons, procurement of training and workshops and the establishment of a separate ICT development unit, although there are still obstacles, especially in human resources. Meanwhile, what needs to be maintained is yellow as a medium with sorogan, bandongan, and deliberation as Islamic methods and values